2016
DOI: 10.1186/s13071-016-1761-5
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasites, growth and physical fitness of schoolchildren in poor neighbourhoods of Port Elizabeth, South Africa: a cross-sectional survey

Abstract: BackgroundAs traditional lifestyle and diets change with social and economic development, disadvantaged communities in low- and middle-income countries increasingly face a double burden of communicable and non-communicable diseases. We studied the relationship between physical fitness and infections with soil-transmitted helminths (STHs), intestinal protozoa and Helicobacter pylori among schoolchildren in Port Elizabeth, South Africa.MethodsWe conducted a cross-sectional survey among 1009 children, aged 9 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
7
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 39 publications
4
38
7
2
Order By: Relevance
“…When viewed from the median value of VO2max in our study, the value of VO2max generated is reaching the average to good value. So in our study, the [12] cardiorespiratory function in infected and non-infected school children with STH was good. This result was probably due to in our study we did not found hookworm infection.…”
Section: Discussionsupporting
confidence: 53%
“…When viewed from the median value of VO2max in our study, the value of VO2max generated is reaching the average to good value. So in our study, the [12] cardiorespiratory function in infected and non-infected school children with STH was good. This result was probably due to in our study we did not found hookworm infection.…”
Section: Discussionsupporting
confidence: 53%
“…However, chronic exposure to enteric infections in infancy may also produce decreased absorption of macro‐ and micronutrients, as well as an increase in systemic inflammation, both able to affect childhood growth. This association was described in some populations where the infection was widespread (Müller et al, ). Soil‐based helminth infestation was common in traditional Sardinia (Palmas et al, ) and may have been an additional causal factor of malnutrition and shortened stature.…”
Section: Infectious Diseasesmentioning
confidence: 62%
“…In 2018, the number of diarrhea sufferers was 1,516,438 [9]. A study from Port Elizabeth South Africa reported that of 934 children, 26% were infected with A. lumbricoides and 22% with T. trichiura [10]. Diarrhea can be caused by infection or non-infection.…”
Section: Introductionmentioning
confidence: 99%